2013
DOI: 10.1165/rcmb.2012-0374oc
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of LPS-Induced Lung Inflammation in Surfactant Protein-C–Deficient Mice

Abstract: Pulmonary surfactant protein-C (SP-C) gene-targeted mice (Sftpc 2/2 ) develop progressive lung inflammation and remodeling. We hypothesized that SP-C deficiency reduces the ability to suppress repetitive inflammatory injury. Sftpc 1/1 and Sftpc 2/2 mice given three doses of bacterial LPS developed airway and airspace inflammation, which was more intense in the Sftpc 2/2 mice at 3 and 5 days after the final dose. Compared with Sftpc 1/1 mice, inflammatory injury persisted in the lungs of Sftpc 2/2 mice 30 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…Pulmonary surfactant proteins are essential for lung function and homeostasis after birth . While surfactant proteins B and C showed a critical role in the preservation of lung function, the immunomodulatory proteins A and D were reported to play an important role during allergic airway inflammation . Here, we show that Igf1r deficiency causes a general increase in surfactant expression basally and after the HDM challenge.…”
Section: Discussionmentioning
confidence: 57%
“…Pulmonary surfactant proteins are essential for lung function and homeostasis after birth . While surfactant proteins B and C showed a critical role in the preservation of lung function, the immunomodulatory proteins A and D were reported to play an important role during allergic airway inflammation . Here, we show that Igf1r deficiency causes a general increase in surfactant expression basally and after the HDM challenge.…”
Section: Discussionmentioning
confidence: 57%
“…We here also assessed the expression of AQP5 in lung tissues and our results showed that increased level of AQP5 was found after the BMMSCs treatment. In addition, previous studies have shown that pulmonary SP-C, an innate immune molecule and presented in alveolar type II cells, could modify lipopolysaccharide (LPS)-induced cell responses (Glasser et al, 2013). We here also examined the expression of SP-C and increased expression of SP-C could be detected in the BMMSCs-treated rats.…”
Section: Discussionmentioning
confidence: 84%
“…Type II cells were isolated using minor modifications of a published procedure [19,20]. Following humane euthanasia, the instillation of Dispase (Gibco) into the lungs of five-week old mice was used to initiate alveolar enzymatic digestion of epithelial cells followed by instillation of low melt agarose to block release and contamination from airway respiratory epithelial cells.…”
Section: Methodsmentioning
confidence: 99%